Proposed new interior design of Lambretta Mazza Centro for Selangor Lambretta Club at 176, Jalan Raja Abdullah, 50300 Kuala Lumpur / Fairuz Aimi Mohammad Azmi - Mohammad Azmi, Fairuz Aimi (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Architecture is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to propose new design of Lambretta Mazza Centro. This proposed club centre is to provide the customers the best services. The target customer are mostly from Lambretta lovers all around Malaysia. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the business. Besides, the concept and images itself should be also related with the theme of the Lambretta. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.